Research on the Phytochemical Analysis of Bidens pilosa L. Leaf Extracts - Mohammad Salim; Rinkoo Vishwakarma (Recent Trends in the Study of Botanical Research Volume - 1, 2023)
Bidens pilosa is a perennial herb found worldwide in temperate and tropical regions. It has a history of traditional use in food and medicine without notable harmful effects. Although there has been progress in analysing its chemical and biological properties, comprehensive and up-to-date reviews are scarce. The plant has shown various pharmacological activities, including hepatoprotective, anti-inflammatory, wound healing, antidiabetic, hypotensive, immunomodulatory effects, and use for conditions like bronchial catarrh, dysentery, and diarrhea. This study focuses on analysing the phytochemicals present in Bidens pilosa leaves. Initially, dried Bidens pilosa powder was extracted using chloroform, acetone-water, and chloroform-water solvents. The extracts were then tested for the presence of different phytochemicals.